Shameful transgressions and intimate boundary works: On gay hook-up app research ethics - Jørgensen, Kristian Møller (AoIR Selected Papers of Internet Research, 2016)
The paper presents and analyses a vignette detailing an affectively charged situation in which the researcher in a meeting with a fellow academic grants and subsequently revokes access to the sexualised profiles of nearby students and faculty members. In relation to this the paper argues that developments within queer, affective theory, as well as sociological and critical notions of intimacy, can shed new light on such challenges that media ethnographers increasingly face. It builds on the work done by queer ethnographic scholars, in that it interrogates not only the actions in fieldwork but also the distinctions and value hierarchies at play, and through that, the norms that put them in place. Further two notions of intimacy is used to asses their analytical and critical potentials for unraveling the chronicled experience of shame.